2022
DOI: 10.1111/exd.14602
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics for the efficacy and side effects of antihistamines

Abstract: Antihistamines, especially H1 antihistamines, are widely used in the treatment of allergic diseases such as urticaria and allergic rhinitis, mainly for reversing elevated histamine and anti‐allergic effects. Antihistamines are generally safe, but some patients experience adverse reactions, such as cardiotoxicity, central inhibition and anticholinergic effects. There are also individual differences in antihistamine efficacy in clinical practice. The concept of individualized medicine has been deeply rooted in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 134 publications
(242 reference statements)
0
22
0
1
Order By: Relevance
“…In addition, there are individual differences in the efficacy of antihistamines in clinical practice. 473 INCS are effective in combating nasal and ocular symptoms and improving quality of life, and are safe for short-term use, but long-term safety data are lacking. Although generally well tolerated, adverse events can be observed that may lead to serious ocular complications.…”
Section: Treatmentmentioning
confidence: 99%
“…In addition, there are individual differences in the efficacy of antihistamines in clinical practice. 473 INCS are effective in combating nasal and ocular symptoms and improving quality of life, and are safe for short-term use, but long-term safety data are lacking. Although generally well tolerated, adverse events can be observed that may lead to serious ocular complications.…”
Section: Treatmentmentioning
confidence: 99%
“…According to the results of the studies mentioned earlier, the reasons why ebastine prolongs the QT interval in some patients and does not in others may be due to the different age groups of the studies, different doses of drugs, drug-drug interactions, and polymorphisms in the genes encoding the P450 cytochrome enzyme systems and histamine receptors of the study individuals. 15…”
Section: Discussionmentioning
confidence: 99%
“…48,49 H1 antihistamines are widely used in the treatment of AR and are generally safe; however, some patients experience adverse reactions, such as cardiotoxicity, central inhibition, and anticholinergic effects. 50 The new-generation antihistamines have proven to be safer, feature faster or equivalent onset of action, and are superior in efficacy compared with first-generation antihistamines, which are recommended by many international bodies as first-line treatment for allergic disease. 51…”
Section: Antihistaminesmentioning
confidence: 99%
“…Due to the effects of histamine‐H1 receptor signaling on the regulation of DC maturation, Th1/Th2 cell balance, eosinophil activity, and cytokine release, H1 antihistamines could also attenuate the symptoms associated with late‐phase allergic reactions 48,49 . H1 antihistamines are widely used in the treatment of AR and are generally safe; however, some patients experience adverse reactions, such as cardiotoxicity, central inhibition, and anticholinergic effects 50 . The new‐generation antihistamines have proven to be safer, feature faster or equivalent onset of action, and are superior in efficacy compared with first‐generation antihistamines, which are recommended by many international bodies as first‐line treatment for allergic disease 51 …”
Section: Treatment Strategies For Armentioning
confidence: 99%